Intention to implement 5S management among students in higher education institutions - Abu Bakar, Nashirah; Uzaki, Kiyotaka; Mohamed Naim, Asmadi; Abd Manaf, Nor Aziah (The Asian Institute of Research, 2020)
The aim of this research paper is to analyze intention for implementing 5S management among students in higher education institutions. The quality management method using 5S approach is function to standardized process to properly implemented creates and maintains an organized, safe, clean and efficient workplace. In this study. The 5S method was implemented to create conducive and efficient place for student activities related to academic. This study implemented quantitative method using survey development with application Technology Acceptance Model, in analyzing student intention of implementing quality management for study workspace and living space. The sampling procedure using stratified random sampling method for students that have intention and experience in implementing quality management in their daily life. The number of respondents is 120 students that studying in higher education institutions. This study developed confirmatory factor analysis for measurement model. The absolute fit index, incremental fit index and parsimonious fit index is meet the requirement level to prove measurement model is robust, reliable and represented the actual data. The structural model in this study analyzed using maximum likelihood estimator. This study indicates all of the exogenous variable have significant and positive effect to the endogenous latent construct. The Perceived Usefulness (PU) has positive and significant direct effect on the Intention (I) to implement 5S quality management. The beta value is positive 0.507 with probability value is less than 0.001. Next, the Perceived Ease of Use (PE) has positive and significant direct effect on the Intention (I) to implement 5S quality management. The beta value is positive 0.433 with probability value is less than 0. 001. Then, the Religiosity (R) has positive and significant direct effect on the Intention (I) to implement 5S quality management. The beta value is positive 0.348 with probability value is less than 0.001. The finding of this study contributes to the body of knowledge in 5S quality management and it helps policy makers in university to develop conducive environment for students.